BODY IMAGE DISORDER LINKED WITH SPORT ACTIVITIES TO OBESITY STUDENTS - Trijayanti Idris, Desi Natalia (Jurnal Penelitian STIKES Kediri, 2012)
Physical changes are very influential on a person's psychological development, and will have an impact on body image, many people are doing the wrong way, whereas sports is a better way. The purpose this study was to determine the correlation body image disorder and sport activities to obesity students at Nursing Study Program S1 STIKES RS Baptis Kediri. The design this study was cross sectional with sample of 71 respondents.Â TheÂ Independent variable was body image disorder and dependent variable was sport activities. Sampling methode used is total sampling, by conducting research using a questionnaire. Data was analyzed by spearman Rho test with a significant value of 0.05. The results of statistical tests, p = 0.038, which means there was a correlation between body image disorder and sports activities of obesity student Nursing Study Program S 1 STIKES RS Baptis Kediri. It can be concluded that there is a correlation between body image disorder and sports activities of obesity student Nursing Study Program S1 STIKES RS Baptis Kediri.